3D Printing Technology in Personalized Drug Formulation and Pharmacy Practice - Nabila Salsabila Yusuf; Muhammad Arslan (Generasi Sains Indonesia, 2026)
This study examines the role of 3D printing technology in personalized drug formulation and pharmacy practice within the context of precision medicine and digital healthcare transformation. Using a systematic literature review approach based on the PRISMA framework, this research analyzed 52 peer-reviewed international journal articles related to pharmaceutical additive manufacturing. The findings indicate that 3D printing technology enhances dosage customization, controlled drug release, medication adherence, and patient-centered pharmaceutical care. The study also highlights the transformation of pharmacy practice from conventional dispensing services toward decentralized and digitally integrated pharmaceutical systems. Oharmacists are increasingly required to develop competencies in digital formulation design, artificial intelligence integration, and precision medicine applications. Despite its significant potential, several challenges remain, including regulatory uncertainty, infrastructure limitations, cybersecurity concerns, and limited professional readiness. The novelty of this study lies in its integrative perspective that combines pharmaceutical technology innovation, pharmacy practice transformation, and healthcare system adaptation within a unified analytical framework.